Políticas públicas de inovação: um estudo em localidades pouco desenvolvidas - Santos, Irllas Evelline de Carvalho (2022)
Brazil has been facing economic and social diversities during the last decades. In this way, opportunities need to be created and challenges overcome for development to thrive and society to develop Brazil has been facing economic and social diversities during the last decades. In this way, opportunities need to be created and challenges overcome for development to thrive and society to develop. Public policies gain prominence for their actions become incentive methods, when they successfully achieve the satisfaction of their actions, providing success for society in innovation, technology and development of the studied localities. The objective of this dissertation is to analyze the adequacy of public innovation policies for the context of underdeveloped localities in the state of Sergipe. The state of Sergipe was chosen because it is the smallest federative unit in the country and has low and sometimes oscillating development rates. For this, the analysis of public policies was rescued and the understanding through the analysis of these policies was developed. The research question that guided this dissertation is: Are public innovation policies appropriate to the context of underdeveloped localities? To this do so, the following specific objectives have been: (1) analyse innovation policies; (2) identify the development purpose behind the policies; and (3) understand the local context of development. Based on the theoretical foundation, categories of analysis were created to characterize the study. This research had a qualitative nature of descriptive character and as a research method was approached a documentary study with interviews and the technique used was the content analysis of Bardin (1977). Data were collected through a search process to the sites of organizations in search of policies and their specific actions in public innovation policies. It is concluded that public innovation policies are not adequate to the context of poorly developed localities because they do not pay attention to the needs of the population and the local context. Often these policies are not effective and consequently end up not reaching most individuals, because they do not have dynamism and articulation during implementation and maturation, something necessary for the proper development of public policies in innovation.